2012
DOI: 10.3109/14767058.2012.733779
|View full text |Cite
|
Sign up to set email alerts
|

Premature rupture of membranes before 34 weeks managed expectantly: maternal and perinatal outcomes in singletons

Abstract: Protective factors for PPROM could be normal AFI, cervical length >25 mm and negative cultures at PPROM diagnosis. These factors could permit home follow-up of this group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
28
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 10 publications
5
28
0
6
Order By: Relevance
“…In the current study, the fetal death rate was 0.6% and the neonatal mortality rate was 7.41%. These figures agree with those found in the literature (17). As expected, the risk of adverse neonatal outcomes declined with a higher gestational age at PPROM; this finding agrees with the results of a study by Pasquier et al (19).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In the current study, the fetal death rate was 0.6% and the neonatal mortality rate was 7.41%. These figures agree with those found in the literature (17). As expected, the risk of adverse neonatal outcomes declined with a higher gestational age at PPROM; this finding agrees with the results of a study by Pasquier et al (19).…”
Section: Discussionsupporting
confidence: 83%
“…This figure disagrees with those reported elsewhere due to differences in inclusion criteria. Ehsanipoor (17). In a retrospective study of women with singleton and twin pregnancies and PPROM between 24 +0 and 36 +6 weeks of gestation, 7.5% were found to have clinical chorioamnionitis (18).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies in the current literature use AFI to determine the perinatal outcomes of oligohydramnios secondary to PPROM [1][2][3][4][5][6][7][8][9][10][11][12][13]. Only two studies [6,7] were identified that assessed perinatal outcomes after PPROM using the SDP and both of these studies were noted to have conflicting results.…”
Section: Introductionmentioning
confidence: 99%
“…PPROM complicates 2-3% of all pregnancies and is associated with 30-40% of preterm deliveries. This condition, therefore, is a major cause of perinatal morbidity and mortality [1,2]. Amniotic fluid has a number of functions that are essential for normal growth and development of the fetus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation